Some Aspects of Emotional Functioning in Hard-of-Hearing Students - Almukhambetova, Bibigul Zheksembaevna; Bazhenova, Elmira Daauletkhanovna; Shuzhebaeva, Arzigul Ismailovna; Dyusembinova, Saule Myrzabekovna; Isabaev, Anuar Toktamysovich (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Input at early ages, hearing loss can compromise emotional health and cause learning difficulties. Nonetheless, there are relatively few relevant investigations addressing emotional development in hearing-impaired students. The current research intended to compare the self-reported emotional functioning in hearing and hearing-impaired students in order to examine whether there are differences between them. A cross-sectional study was conducted on 94 hard-of-hearing individuals and 104 typical hearing subjects between 16 and 24 years of age from three institutions in Kazakhstan. The overall happiness, life satisfaction, level of anxiety, and emotional preferences were assessed with the Subjective Happiness Scale, Satisfaction with Life Scale, State-Trait Anxiety Inventory, and a questionnaire developed by Dodonov, respectively. The data were subjected to the multivariate analysis of variance. Children and adolescents with hearing loss are reportedly more likely than typical hearing peers to experience various psychosocial difficulties, antisocial disorders, and reactions. However, in the present research, both groups were similar regarding the emotional preferences, apart from the altruistic scale, which was significantly higher (P <0.001) in hearing-impaired participants relative to their hearing counterparts. When compared to normal-hearing persons, hard-of-hearing respondents had higher scores (P <0.001) for trait and state anxiety while having lower scores (P ≤0.001) for satisfaction with life and overall happiness, which could be seen as a matter of concern. As a potential future line of research, throwing more light on other aspects of emotional functioning in learners with hearing loss might be necessary. To our knowledge, this is the first report on the State-Trait Anxiety Inventory performed on hearing-impaired youth. The findings from this investigation could be of practical help to practitioners working with hard-of-hearing students, providing additional information on their emotional well-being.